1995
DOI: 10.1016/1074-7613(95)90126-4
|View full text |Cite
|
Sign up to set email alerts
|

Impaired proliferation of peripheral B cells and indication of autoimmune disease in lyn-deficient mice

Abstract: The Src family protein-tyrosine kinase Lyn associates physically with the BCR and has been suggested to play an important role in BCR-mediated signaling. Studies with lyn-/- mice showed that the number of B cells decreased by half in their peripheral tissues. In addition, these B cells do not respond normally to a number of stimuli, including BCR cross-linking and CD40 ligand. Induction of tyrosine phosphorylation on a variety of cellular proteins, such as Vav, Cbl, and HS1, upon BCR cross-linking was also abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

35
400
4

Year Published

1997
1997
2008
2008

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 442 publications
(439 citation statements)
references
References 60 publications
35
400
4
Order By: Relevance
“…For example, significant evidence exists to suggest that in B cells, early responses to BCR cross-linking are altered in Lyn −/− mice, supporting a role for Lyn in the initiation of signaling via the BCR [20,21,23]. Intriguingly, Lyn-deficient B cells are also hyperresponsive to anti-IgMinduced proliferation and demonstrate enhanced activation of mitogen-activated protein kinase and sustained calcium mobilization [21][22][23]26]. Hernandez-Hansen et al [32] have shown that dysregulated signaling in Lyn-deficient mast cells is due in part to enhanced Fyn activation, and a recent study by Hong et al [33] suggested that the Src kinase Hck regulates mast cell activation by suppressing activation of Lyn.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, significant evidence exists to suggest that in B cells, early responses to BCR cross-linking are altered in Lyn −/− mice, supporting a role for Lyn in the initiation of signaling via the BCR [20,21,23]. Intriguingly, Lyn-deficient B cells are also hyperresponsive to anti-IgMinduced proliferation and demonstrate enhanced activation of mitogen-activated protein kinase and sustained calcium mobilization [21][22][23]26]. Hernandez-Hansen et al [32] have shown that dysregulated signaling in Lyn-deficient mast cells is due in part to enhanced Fyn activation, and a recent study by Hong et al [33] suggested that the Src kinase Hck regulates mast cell activation by suppressing activation of Lyn.…”
Section: Discussionmentioning
confidence: 99%
“…Lyn −/− mice are hyperresponsive to myeloid growth factors and develop a myeloproliferative disorder due, in part, to loss of negative regulation through SHP-1 and SHIP phosphatases [19]. The importance of regulating Lyn activation is further demonstrated by additional pathological changes that occur in Lyndeficient mice, including lethal antibody-mediated autoimmune disease [20][21][22][23]. Lyndeficient mice succumb to autoimmune disease, and B cells from Lyn-deficient mice demonstrate hypersensitivity to B-cell receptor (BCR) stimulation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…B cells from mice deficient in Lyn (10)(11)(12), CD22 (13)(14)(15)(16), SHP-1 (17,18) exhibit a hyperreactive phenotype and produce autoantibodies. Indeed, Lyn-deficient mice demonstrate activation of autoreactive B cells and subsequent SLE-like symptoms, such as the production of anti-double-stranded DNA (anti-dsDNA) antibodies, splenomegaly, and glomerulonephritis (11,12).…”
mentioning
confidence: 99%
“…Indeed, Lyn-deficient mice demonstrated the activation of autoreactive B lymphocytes and subsequent SLE-like symptoms, such as the production of anti-double-strand DNA antibody, splenomegaly and glomerulonephritis. 25,26 Moreover, it is shown that lupus B lymphocytes exhibit aberrant BCRmediated signal transduction. 13 These data prompted us to investigate BCR-associated signaling molecules in SLE patients.…”
Section: Introductionmentioning
confidence: 99%